Phytochemicals, nutritional, anti-nutritional and bioactivity of Dioscorea pentaphylla L. tuber : A review: Fitokimia, Nutrisi, Anti Nutrisi dan Bioaktivitas Umbi Tomboreso (Dioscorea pentaphylla L.): Kajian Pustaka - Witoyo, Jatmiko Eko; Hamaisa, Atika; Utoro, Panggulu Ahmad Ramadhani (Universitas Slamet Riyadi Surakarta, 2025)
Dioscorea pentaphylla L. tubers, locally known as tomboreso tubers by Indonesian people, grow wild in forests in various parts of Indonesia but are not well-underutilized. This article aims to comprehensively review the phytochemistry, nutritional, anti-nutritional, and bioactivity of tomboreso tubers. The method used is a literature study with a database of online articles downloaded from Google Scholar related to the topic discussed. Various earlier studies reported that tomboreso tubers are rich in phytochemical compounds, such as alkaloids, flavonoids, polyphenols, terpenoids, tannins, glycosides, and saponins. Tomboreso tubers are also rich in complete nutritional content, such as protein content (1.69-9.20%), fat (0.14-6.24%), fiber (1.28-7.24%), starch (3.71-61.26%), minerals, amino acids, and fatty acids. Furthermore, tomboreso tubers also contain anti-nutritional compounds that are less beneficial to health, such as tannins, oxalates, hydrogen cyanide, phenols, flavonoids, phytates, a-amylase inhibitors, and trypsin inhibitors. Tomboreso tubers have been shown to have various biological activities, such as anti-bacterial, anti-mutagenic, and antioxidant, from various earlier studies. To make tomboreso tubers safe to eat and an alternative food source with low anti-nutritional content, further research must be done on their exploration, utilization, and further processing to reduce anti-nutritional compounds.